Pengaruh Tipe Kepemimpinan Orangtua Terhadap Proses Sosialisasi Pada Siswa : Studi Kasus SMP Negeri 3 Pematang Jaya Satu Atap - Hendrianto Hendrianto; Ersika Puspita Dani (Cendikia : Media Jurnal Ilmiah Pendidikan, 2020)
What is expressed in this study is how much influence of the type of parental leadership on the socialization process of students. The research sample studied was a student of SMP Negeri 3 Pematang Jaya Satu Atap as many as 40 people. The method used is descriptive method. To obtain the data, the researchers used a closed questionnaire. The data obtained in its processing is adjusted to the criteria of item number 1 to 22, namely: 1.00-0.66 included in the category of authoritarian leadership types, 1.67 -2.33 is the leadership type laizer Faire, 2.34-3.00 including the democratic type. For items 23 to d 45 use 1.00–1.75 less once, 1.76 – 2.50 less, 2.51 – 3.25 good, and 3.26–4.00 including an excellent socialization process. The hypothesis that is enforced is that there is a meaningful influence between the type of parental leadership in the family to the socialization process of children (students). The analysis technique used is a quantitative data analysis technique, while to find out the correlation of X and Y, the author uses pearson correlation formula: From the results of calculations, the type of leadership of parents of students is mostly Laizer Faire. While the correlation between the two variables is positive where rcalculates the > rof thetable, namely r(h) 0.99 > r(t) 0.312. So the hypothesis is accepted that there is an influence of the type of parental leadership in the family on the socialization process of students. To see the magnitude of the influence exerted from the results of calculations obtained 98%. Thus, there is a positive and meaningful influence between parental leadership on the socialization process in students.